2021
DOI: 10.3390/agriculture11040324
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cooling and Heating Systems on Pen Fouling, Lying Behavior, and Performance of Rearing Piglets

Abstract: The rearing of piglets is a demanding phase of pig production partly because of the changing temperature requirements of the piglets during rearing. Piglets need high temperatures in the resting area, especially at the beginning, while the optimal temperature is lower toward the end of rearing. To meet the changing temperature demands of the piglets and also to optimize the pen structure, one floor cooling and two heating systems were examined in this study. In two rearing compartments, four pens with 48 pigle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…Thus, pigs seem to avoid eliminating where they lie if the conditions allow it [ 37 , 38 ]. These findings are in accordance with the studies of Opderbeck et al [ 39 ] and Taylor et al [ 20 ] who found that pigs preferred to defaecate in the brightly lit areas. The ability to minimize soiling to specific areas of the pen offers advantages in terms of air quality in the area where the pigs are staying, as well as manure management.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, pigs seem to avoid eliminating where they lie if the conditions allow it [ 37 , 38 ]. These findings are in accordance with the studies of Opderbeck et al [ 39 ] and Taylor et al [ 20 ] who found that pigs preferred to defaecate in the brightly lit areas. The ability to minimize soiling to specific areas of the pen offers advantages in terms of air quality in the area where the pigs are staying, as well as manure management.…”
Section: Discussionsupporting
confidence: 93%
“…The most favorable conditions for breeding prenursery pigs can be ensured by the application of combined heating when the heat is transferred to the animals both from the bottom and from overhead with the help of infrared thermal radiation and heated floors, panels or mats [6][7][8][9]. Heating is mainly achieved by the use of either electric resistance heaters or hot water [10][11][12][13]. In order to maintain standard microclimate parameters in animal-breeding premises, a complex energy-saving heat-provision system has been designed, comprising an electric thermal storage (ETS) unit and overhead fan [14].…”
Section: Introductionmentioning
confidence: 99%